2021
DOI: 10.21608/esj.2022.113702.1207
|View full text |Cite
|
Sign up to set email alerts
|

Cervical Discopathy in Idiopathic Trigeminal Neuralgia: More than Coincidence?

Abstract: Background Data: The most common cause of trigeminal neuralgia is neurovascular compression. However, several patients present with unknown etiology. Purpose: This study aims to investigate the relationship between trigeminal neuralgia and cervical pathology in patients previously diagnosed with idiopathic trigeminal neuralgia. Study Design: We designed an observational case-control study in our tertiary center. Patients and Methods: A study group consisting of patients previously diagnosed with idiopathic tri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…Given the uncertainties regarding the source of TN, there has been an increasing focus on pathology of the spinal trigeminal nucleus, also called the trigeminal tract, as a potential etiology 5,6 . Several recent case reports have highlighted a potential link between degenerative conditions affecting the cervical spine and development of TN 7–11 .…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Given the uncertainties regarding the source of TN, there has been an increasing focus on pathology of the spinal trigeminal nucleus, also called the trigeminal tract, as a potential etiology 5,6 . Several recent case reports have highlighted a potential link between degenerative conditions affecting the cervical spine and development of TN 7–11 .…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge, the potential association between TN and DCM has only been explored by one study larger than a case report or series 5 . This recent case–control study, which included 20 individuals, found a significant association between cervical disc displacement causing indentation on the cervical spinal cord superior to the C4 vertebra and symptoms of TN 5 .…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations